A Concentric Ring Electrode for a Wall‐jet Cell in a Microfluidic Device. Issue 9 (6th June 2019) - Nishiyama, Keine; Hoshikawa, Koki; Maeki, Masatoshi; Ishida, Akihiko; Tani, Hirofumi; Tokeshi, Manabu
Abstract: A concentric ring array electrode that amplifies the current signal without redox cycling has been developed for highly sensitive electrochemical detection at a single potential in a microfluidic platform. Herein, the effect of ring‐electrode width on the current and current density was examined. A ring‐array electrode with widths that decrease from the inner to the outer ring was shown to exhibit the highest sensitivity. This electrode delivered a current density that was approximately 50 % higher than that of a conventionally used disc electrode. We used numerical simulations to further optimize this type of array electrode, which led to a limit of detection for catechol of 6.2 nmol/L. This ring array electrode has great potential for use in a variety of applications because it can be used to detect irreversible targets with a simple apparatus at a single potential and requires no electrode modification to achieve high sensitivity. Abstract :